Assessment of weight gain following adenotonsillectomy in children with Down syndrome. (September 2017) - D'Esposito, Christopher F.; Farhood, Zachary; Baker, Andrew B.; Nguyen, Shaun A.; LaRosa, Angela C.; Lal, Chitra; White, David R.
Abstract: Introduction: Adenotonsillectomy (T&A) has been associated with postoperative weight gain in children. The purpose of this study is to determine whether a similar association exists in children with Down syndrome (DS). Methods: The medical records of 311 DS patients were reviewed. Subjects were classified into either a control group or surgical group based on whether they had undergone adenotonsillectomy (T&A). Subjects were excluded if they only had one recorded BMI. Cases were analyzed in a pairwise fashion to maximize available data. 113 total patients with DS were identified: 84 (74.3%) in the control group and 29 (25.7%) in the T&A group. Height, weight, BMI, and Z-score data were compared between the control and T&A groups at 6-month intervals over a 24-month period. Results: Children with DS who underwent T&A were comparable by demographics to children with DS who did not undergo T&A. Mean weight gain at 24 months for the T&A group was 8.07 ± 5.66 kg compared with 5.76 ± 13.20 kg in controls. The median Z-score at 24 months for the T&A group was 1.11 (0.10–1.88) compared with 1.17 (0.80–1.75) in controls. Children undergoing T&A had a stable median Z-score change of 0.09 at 24 months (p = 0.861, compared to baseline) while children who did not undergo T&A had a significantly increased median Z-score of 0.52 (p = 0.035, compared to baseline). Despite this, there were no significant intergroup differences between weight change, BMI, nor Z-score at any interval (p > 0.05). Conclusions and relevance: Children with DS did not have an increased rate of weight gain or increased BMI after T&A. BMI Z-scores were shown to stabilize over 24 months in the T&A group and increase in the control group. While this suggests that T&A provides an added benefit of weight control in patients with DS, the results should be interpreted with caution due to the small sample size and the fact that not all patients had complete follow up across a 24-month period.